UJI KELAYAKAN MEDIA VIRTUAL REALITY (VR) BERBASIS ARTSTEPS DENGAN METODE PERMAINAN TEKA-TEKI PADA PEMBELAJARAN BAHASA JEPANG DI TINGKAT SMA - Hifzy Aldiansyah; Cut Erra Rismorlita (Universitas Negeri Jakarta, 2026)
Technological developments occur very rapidly, learning in schools, especially at the high school level in Indonesia, still uses conventional media, therefore alternative learning media that use current technology are needed so that learning becomes more varied and enjoyable. This study aims to determine the feasibility of Artsteps-based Virtual Reality (VR) media as a Japanese language learning medium at the high school level and to determine students' responses or reactions after using Artsteps media. The subjects of this study were media experts, material experts, and grade XI students of SMA Negeri 75 Jakarta. This study uses a qualitative descriptive method. This study applies data collection methods in the form of a media feasibility assessment rubric by Media experts, a material feasibility assessment rubric by material experts, and a questionnaire given to students after using Artsteps media. The data analysis technique applied is a descriptive analysis technique to process data from the validation results of media and material feasibility by calculating the assessment scores from experts. The results of this study show that the level of media feasibility by Media Experts obtained a score of 70%, with the criteria of being feasible. The level of material feasibility by Material Experts obtained a score of 70% with the criteria of being feasible. Based on the validation results from these experts, Artsteps-based Virtual Reality media is declared feasible. Despite being declared feasible, in practice in the eleventh grade of SMA Negeri 75 Jakarta, the Artsteps-based Virtual Reality (VR) media was declared unfeasible due to two main problems. First, the lack of support for students' Smartphones in running the Artsteps application. Second, inadequate internet access hampered the learning process using Artsteps media, which heavily requires internet access. This was supported by numerous student responses complaining about internet problems and unsupported Smartphones, making Artstep media unpleasant and unsuitable for use in Japanese language learning.